2022
DOI: 10.3390/ijerph19105784
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity, Involvement, and Nostalgia in Heritage Hotels in the Era of Digital Technology: A Moderated Meditation Model

Abstract: Heritage hotels attract a large number of foreign and domestic tourists by offering luxurious experiences while also providing an opportunity to learn about the history, art, culture, tastes, traditions, and sentiments present in various eras in a region’s history. The literature on heritage lodging buildings is still sparse, limited, and lacking in well-established empirical evidence. The purpose of this study is to examine the relationships between perceived authenticity, visitor involvement, and nostalgia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Along these same lines, earlier research has confirmed the link between love and destination identification [41,42]. In this regard, the researchers pointed out that the development and enhancement of positive sentiments towards tourism destinations are crucial for encouraging favorable visitor behavior [5,43] and resistance to a harmful attitude [44]. Thus, tourists who have these feelings resulting from destination identification may be more concerned about the destination environment and have favorable attitudes toward preserving this destination environment because they view themselves as part of it [23].…”
Section: Destination Identification (Di) and Tourists' Sustainable Us...mentioning
confidence: 78%
See 1 more Smart Citation
“…Along these same lines, earlier research has confirmed the link between love and destination identification [41,42]. In this regard, the researchers pointed out that the development and enhancement of positive sentiments towards tourism destinations are crucial for encouraging favorable visitor behavior [5,43] and resistance to a harmful attitude [44]. Thus, tourists who have these feelings resulting from destination identification may be more concerned about the destination environment and have favorable attitudes toward preserving this destination environment because they view themselves as part of it [23].…”
Section: Destination Identification (Di) and Tourists' Sustainable Us...mentioning
confidence: 78%
“…In recent years, there has been a noticeable surge in global interest towards sustainable tourism [1][2][3], driven by escalating concerns surrounding environmental preservation and the safeguarding of cultural heritage [4][5][6][7]. At the core of this discourse lies the conduct of residents and tourists within destination locales [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, three criteria were implemented to assess the discriminant validity of the constructs. They were cross-loading, Fornell-Larcker criterion, and heterotrait-monotrait ratio (HTMT) [101,103]. As indicated in Table 2, the outer loading for each latent variable bolded was higher than the cross-loading with other measurements.…”
Section: Assessment Of Outer Measurement Modelmentioning
confidence: 95%
“…Additionally, in response to green guest pressure, and in an effort to be more environmentally consciously, restaurants have made attempts to source some of their ingredients locally (farm-to-fork (FTF) approach) [52]. Thus, by adopting and promoting the principles of the farm-to-fork (FTF) concept, hotels and restaurants can satisfy customers' needs for an authentic and high-quality experience [53], as well as local food experiences. In short, by adopting the principles of the farm-to-fork (FTF) concept, the local rural community (sustainable agriculture practices), restaurants, and hotels reciprocate the benefits.…”
Section: Theoretical Foundations and Hypotheses Formulationmentioning
confidence: 99%